Preparation method of optical cable and corrosion-resistant coating for immersion liquid-cooled data center
By applying corrosion-resistant coating containing fluorosilicon modified hollow SiO2 material on the optical cable, the problem of swelling of the coolant on the optical cable coating is solved, and the service life and corrosion resistance of the optical cable are improved.
Patent Information
- Application Number
- CN202411593206.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-11-08
AI Technical Summary
In the immersed liquid-cooled data center, the coolant swells the polymer cladding of the optical cable, causing external organic molecules and water vapor to enter the optical cable, corroding the optical fibers, and shortening the service life of the optical cable.
The corrosion-resistant coating containing fluorosilicone modified hollow SiO2 material is adopted to increase the roughness of the coating through irregularly arranged micro-nano particles, reduce wetting, and effectively block external corrosive substances through fluorosilicone modified hollow SiO2 material with high density and low surface energy.
Improves the service life of optical cables in immersed liquid-cooled data centers, and reduces the risk of fiber corrosion damage by enhancing the roughness and corrosion resistance of the fiber surface.
Smart Images

Figure CN119087612B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of optical equipment, and in particular to a method for preparing an optical cable and an anti-corrosion coating for an immersion liquid-cooled data center. Background Art
[0002] An immersion liquid-cooled data center is a data center that uses coolant as a cooling medium. The equipment in the immersion liquid-cooled data center is immersed in the coolant to remove heat through the coolant. The equipment (such as optical communication modules) is connected through optical cables, and these optical cables are immersed in the coolant for a long time.
[0003] The coolant is usually composed of organic compounds. Since these organic compounds have a strong swelling ability for polymer materials, after long-term immersion, the coolant will cause the polymer coating on the outside of the optical cable to swell, causing external organic molecules, water vapor and other corrosive substances to enter the interior of the optical cable, which in turn causes the optical fiber inside the optical cable to be corroded by organic molecules and water vapor and damaged, affecting the service life of the optical cable. Summary of the invention
[0004] In order to solve the above technical problems, the present application discloses a method for preparing an optical cable and an anti-corrosion coating for an immersion liquid-cooled data center, so as to increase the service life of the optical cable in the application scenario of the immersion liquid-cooled data center.
[0005] In the first aspect, the present application provides an optical cable for an immersion liquid-cooled data center, the optical cable comprising a core layer, an optical fiber being arranged in the core layer, an anti-corrosion coating being arranged on the outer surface of the core layer, the outer surface of the anti-corrosion coating also comprising a cladding layer, the anti-corrosion coating containing a fluorine-silicon modified hollow SiO2 material, the fluorine-silicon modified hollow SiO2 material comprising a first hollow SiO2 material and a second hollow SiO2 material, the average particle size of the first hollow SiO2 material being 20nm~50nm, and the average particle size of the second hollow SiO2 material being 200nm~300nm.
[0006] In some embodiments of the present application, the mass ratio of the first hollow SiO2 material to the second hollow SiO2 material is (0.2-0.5):1.
[0007] In some embodiments of the present application, the anti-corrosion coating also contains magnesium fluoride, the mass percentage of the magnesium fluoride in the anti-corrosion coating is 1%~10%, and the mass percentage of the fluorine-silicon modified hollow SiO2 material in the anti-corrosion coating is 90%~99%.
[0008] In some embodiments of the present application, the thickness of the anti-corrosion coating is 1 μm to 100 μm.
[0009] In some embodiments of the present application, the number of the core layer is single;
[0010] Alternatively, the number of the core layers is N, and the outer surface of each core layer is provided with the anti-corrosion coating, wherein 2≤N≤32.
[0011] In some embodiments of the present application, the coating layer includes a buffer layer and a first protective layer, the buffer layer is disposed on the outer surface of the anti-corrosion coating, and the first protective layer is disposed on the outer surface of the buffer layer.
[0012] In some embodiments of the present application, the coating layer further includes a second protective layer, and the second protective layer is disposed between the anti-corrosion coating and the buffer layer.
[0013] In some embodiments of the present application, the Shore hardness of the first protective layer is 80A-95A, and the Shore hardness of the second protective layer is 48D-55D;
[0014] and / or, the oxygen index of the first protective layer and the second protective layer is not less than 32;
[0015] And / or, the material of the first protective layer and the second protective layer is selected from at least one of thermoplastic polyurethane elastomer, polyimide, polyvinylidene fluoride, polybutylene terephthalate and polyphenylene sulfide.
[0016] In some embodiments of the present application, the first protective layer and the second protective layer further contain a flame retardant, and the flame retardant is compounded by an organic hypophosphite flame retardant and a melamine compound;
[0017] And / or, the organic hypophosphite flame retardant includes at least one of methyl aluminum hypophosphite, methylethyl aluminum hypophosphite, phenyl aluminum hypophosphite, divinyl aluminum hypophosphite, divinyl zinc hypophosphite and microcapsule-based phenyl aluminum hypophosphite; the melamine compound includes at least one of melamine pyrophosphate, melamine polyphosphate and microcapsule-based melamine cyanurate.
[0018] In a second aspect, the present application provides a method for preparing an anti-corrosion coating, comprising the following steps:
[0019] After aluminum isopropoxide, perfluorooctyltriethoxysilane, ethanol, water and glacial acetic acid are uniformly mixed at room temperature, ethyl orthosilicate is added and mixed again uniformly, and sodium hydroxide solution is added dropwise until the pH value of the system is 10-12 to obtain a sol containing the first hollow SiO2 material;
[0020] After aluminum isopropoxide, perfluorooctyl triethoxysilane, ethanol, water and ammonia water are uniformly mixed at room temperature, ethyl orthosilicate is added and mixed again uniformly, and sodium hydroxide solution is added dropwise until the pH value of the system is 10-12 to obtain a sol containing a second hollow SiO2 material;
[0021] The prepared sol containing the first hollow SiO2 material and the sol containing the second hollow SiO2 material are mixed according to a target ratio to obtain a sol containing the fluorine-silicon modified hollow SiO2 material;
[0022] The sol containing the fluorine-silicon modified hollow SiO2 material is coated on the surface of the optical cable core layer, and the anti-corrosion coating is obtained after drying.
[0023] Compared with the prior art, this application has at least the following beneficial effects:
[0024] The present application provides a method for preparing an optical cable and an anti-corrosion coating for an immersed liquid-cooled data center, wherein the optical cable includes a core layer, an optical fiber is arranged in the core layer, and an anti-corrosion coating is arranged on the outer surface of the core layer, and the anti-corrosion coating contains a fluorine-silicon modified hollow SiO2 material, wherein the average particle size of the first hollow SiO2 material is 20nm~50nm, and the average particle size of the second hollow SiO2 material is 200nm~300nm. In this way, different micro-nano particles are arranged irregularly, and the surface of the anti-corrosion coating is rougher and has a micro-nano multi-scale rough structure, thereby reducing the wettability. The increase in the roughness of the optical fiber surface is crucial for the construction of a super oleophobic surface, which helps to improve the material's resistance to coolant. In addition, the above-mentioned fluorine-silicon modified hollow SiO2 material has high density and low surface energy, and can effectively block external corrosive substances such as organic molecules and water vapor from entering the interior of the optical cable, thereby reducing the risk of corrosion and damage to the optical fiber inside the optical cable, and improving the service life of the optical cable in the application scenario of the immersed liquid-cooled data center. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0026] Figure 1 This is a schematic diagram of the structure of an optical cable used for an immersion liquid-cooled data center in one embodiment of the present application;
[0027] Figure 2 This is a schematic diagram of the structure of an optical cable used for an immersion liquid-cooled data center in another embodiment of the present application;
[0028] Figure 3This is a schematic diagram of the structure of an optical cable used for an immersion liquid-cooled data center in another embodiment of the present application;
[0029] Figure 4 This is a schematic diagram of the structure of an optical cable used in an immersion liquid-cooled data center in another embodiment of the present application.
[0030] Explanation of the reference numerals: 1 - core layer, 2 - anti-corrosion coating, 3 - cladding layer, 11 - optical fiber, 30 - buffer layer, 31 - first protective layer, 32 - second protective layer. DETAILED DESCRIPTION
[0031] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0032] In the present application, the terms "upper", "lower", "left", "right", "front", "back", "top", "bottom", "inner", "outer", "vertical", "horizontal", "lateral", "longitudinal" and the like indicate positions or positional relationships based on the positions or positional relationships shown in the drawings. These terms are mainly used to better describe the present application and its embodiments, and are not used to limit the indicated devices, elements or components to have a specific orientation, or to be constructed and operated in a specific orientation.
[0033] In addition, some of the above terms may be used to express other meanings in addition to indicating orientation or positional relationship. For example, the term "on" may also be used to express a certain dependency or connection relationship in some cases. For those of ordinary skill in the art, the specific meanings of these terms in this application can be understood according to specific circumstances.
[0034] In addition, the terms "installed", "set", "provided with", "connected", and "connected" should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral structure; it can be a mechanical connection, or an electrical connection; it can be a direct connection, or an indirect connection through an intermediate medium, or it can be an internal connection between two devices, elements, or components. For those of ordinary skill in the art, the specific meanings of the above terms in this application can be understood according to specific circumstances.
[0035] In addition, the terms "first", "second", etc. are mainly used to distinguish different devices, elements or components (the specific types and structures may be the same or different), and are not used to indicate or imply the relative importance and quantity of the indicated devices, elements or components. Unless otherwise specified, "plurality" means two or more.
[0036] The present application provides an optical cable for an immersion liquid-cooled data center, such as Figure 1 As shown, the optical cable includes a core layer 1, an optical fiber 11 is arranged in the core layer 1, and an anti-corrosion coating 2 is arranged on the outer surface of the core layer 1. The anti-corrosion coating 2 contains a fluorine-silicon modified hollow SiO2 material, and the fluorine-silicon modified hollow SiO2 material includes a first hollow SiO2 material and a second hollow SiO2 material. The average particle size of the first hollow SiO2 material is 20nm~50nm, and the average particle size of the second hollow SiO2 material is 200nm~300nm. In addition, the outer surface of the anti-corrosion coating 2 also includes a coating layer 3, and the number of the coating layer 3 is at least one. The coating layer can be made of polymer materials and has the functions of protection, flame retardancy, buffering, etc.
[0037] The inventors have found that the coolant in immersion liquid-cooled data centers is usually composed of compounds. After the optical cable has been immersed in the coolant for a long time, the outer coating swells, causing the organic molecules of the coolant and the water vapor in the coolant to enter the interior of the optical cable, and the optical fibers inside the optical cable are corroded by the organic molecules and water vapor. Based on this, the anti-corrosion coating of the present application contains fluorine-silicon modified hollow SiO2 material, wherein the average particle size of the first hollow SiO2 material is 20nm~50nm, and the average particle size of the second hollow SiO2 material is 200nm~300nm. In this way, different micro-nano particles are arranged irregularly, and the surface of the anti-corrosion coating is rougher, with a micro-nano multi-scale rough structure, thereby reducing the wettability. The increase in the surface roughness of the optical fiber is crucial for the construction of a super oleophobic surface, which helps to improve the coolant resistance of the material. In addition, the above-mentioned fluorine-silicon modified hollow SiO2 material has high density and low surface energy. Even if the coating layer outside the core layer swells due to the coolant, it can effectively block external corrosive substances such as organic molecules and water vapor from entering the interior of the optical cable, thereby reducing the risk of corrosion and damage to the optical fiber inside the optical cable, and improving the service life of the optical cable in the application scenario of submerged liquid-cooled data centers.
[0038] In an optional embodiment, the mass ratio of the first hollow SiO2 material to the second hollow SiO2 material is (0.2-0.5):1.
[0039] In an optional embodiment, the anti-corrosion coating further contains magnesium fluoride, which is beneficial to reduce the refractive index of the anti-corrosion coating, so that the optical fiber coated inside the anti-corrosion coating has better optical performance.
[0040] In an optional embodiment, the mass percentage of magnesium fluoride in the anti-corrosion coating is 1%~10%, and the mass percentage of fluorine-silicon modified hollow SiO2 material in the anti-corrosion coating is 90%~99%, which is conducive to obtaining an anti-corrosion coating that can both block external corrosive substances and reduce the refractive index of the optical fiber to improve the optical performance.
[0041] In an optional embodiment, the thickness of the anti-corrosion coating is 1 μm to 100 μm; in other embodiments, the thickness of the anti-corrosion coating is 5 μm to 30 μm. The inventors have found that when the thickness of the anti-corrosion coating is too small, it is difficult to effectively block external corrosive substances from entering the core layer; when the thickness of the anti-corrosion coating is too large, the adhesion between the anti-corrosion coating and the core layer decreases, causing the anti-corrosion coating to be easily peeled off, affecting the life of the optical cable. By regulating the thickness of the anti-corrosion coating within the above range, it is beneficial to obtain an anti-corrosion coating that can block external corrosive substances and has high adhesion strength, which is beneficial to increase the service life of the optical cable in the coolant of an immersion liquid-cooled data center.
[0042] In an optional embodiment, reference Figure 1 , the number of core layers is one; in another embodiment, the number of core layers is N, 2≤N≤32. Figure 2 The number of core layers 1 in an optical cable is 7, and the outer surface of each core layer 1 is provided with an anti-corrosion coating 2, which improves the transmission performance of the optical cable while protecting each core layer in the optical cable from being corroded by external corrosive substances.
[0043] In an optional embodiment, reference Figure 3 The coating layer 3 includes a buffer layer 30 and a first protective layer 31, which are sequentially arranged on the surface of the anti-corrosion coating 2. The buffer layer and the first protective layer may include different types of polymer materials, wherein the buffer layer plays a protective and buffering role and may be formed by weaving aramid fibers; the first protective layer plays a protective and flame-retardant role to further protect the optical cable.
[0044] In an optional embodiment, reference Figure 4 The coating layer 3 further includes a second protective layer 32, which is disposed between the anti-corrosion coating 2 and the buffer layer 30. The second protective layer and the first protective layer may have the same polymer material, which plays a protective and flame-retardant role to further protect the optical cable.
[0045] In an optional implementation, the Shore hardness of the first protective layer is 80A-95A, and the Shore hardness of the second protective layer is 48D-55D. The first protective layer is harder, and the second protective layer is softer, so that the harder first protective layer not only plays a protective and flame-retardant role, but also plays a role in improving the structural strength of the optical cable; the softer second protective layer not only plays a protective and flame-retardant role, but also plays a role in absorbing external impact.
[0046] In an optional embodiment, the oxygen index of the first protective layer and the second protective layer is not less than 32, and has excellent flame retardancy.
[0047] The present application has no particular restrictions on the materials of the first protective layer and the second protective layer, which can be selected from polymer materials. For example, the materials of the first protective layer and the second protective layer include but are not limited to at least one of thermoplastic polyurethane elastomer, polyimide, polyvinylidene fluoride, polybutylene terephthalate and polyphenylene sulfide materials.
[0048] In an optional embodiment, the first protective layer and the second protective layer also contain a flame retardant, which is a compound of an organic hypophosphite flame retardant and a melamine compound, wherein the organic hypophosphite flame retardant includes at least one of methyl aluminum hypophosphite, methylethyl aluminum hypophosphite, phenyl aluminum hypophosphite, divinyl aluminum hypophosphite, divinyl zinc hypophosphite and microcapsule-based phenyl aluminum hypophosphite; and the melamine compound includes at least one of melamine pyrophosphate, melamine polyphosphate and microcapsule-based melamine cyanurate.
[0049] The present application also provides a method for preparing an anti-corrosion coating, comprising the following steps:
[0050] Preparation of fluorine-silicon modified hollow SiO2 materials:
[0051] Step A, after mixing aluminum isopropoxide, perfluorooctyl triethoxysilane, ethanol, water and glacial acetic acid at room temperature, adding tetraethyl orthosilicate (TEOS) and mixing again, continuing to stir, and adding sodium hydroxide solution dropwise until the pH value of the system is 10-12, to obtain a sol containing a first hollow SiO2 material;
[0052] Step B, after mixing aluminum isopropoxide, perfluorooctyltriethoxysilane, ethanol, water and ammonia water at room temperature, adding EOS and mixing again, continuing to stir, adding sodium hydroxide solution dropwise until the pH value of the system is 10-12, to obtain a sol containing a second hollow SiO2 material;
[0053] Step C: Mixing the prepared sol containing the first hollow SiO2 material and the prepared sol containing the second hollow SiO2 material according to a target ratio to obtain a sol containing fluorine-silicon modified hollow SiO2 material.
[0054] Preparation of anti-corrosion coating:
[0055] Step D: coating the sol containing the fluorine-silicon modified hollow SiO2 material on the surface of the optical cable core layer, and drying at 80° C. to 120° C. to obtain an anti-corrosion coating.
[0056] In another embodiment, for step B, the sol containing the fluorine-silicon modified hollow SiO2 material can be mixed with magnesium fluoride, and the resulting anti-corrosion coating slurry can be coated on the surface of the optical cable core layer, and the anti-corrosion coating can be obtained after drying.
[0057] The present application has no particular restrictions on the preparation methods of the buffer layer, the first protective layer and the second protective layer, as long as the purpose of the present application can be achieved. For example, the buffer layer can be woven from polymer fibers; the first protective layer and the second protective layer can be prepared by a sheath extrusion device.
[0058] In one embodiment, a buffer layer and a first protective layer can be prepared in sequence on the surface of the anti-corrosion coating, and the first protective layer serves as an outer sheath; in another embodiment, a second protective layer, a buffer layer and a first protective layer can be prepared in sequence on the surface of the anti-corrosion coating, and the second protective layer serves as an inner sheath.
[0059] The present application does not particularly limit the method for regulating the average particle size of the first hollow SiO2 material. For example, in the above step A, the average particle size of the first hollow SiO2 material can be regulated by regulating the concentration of the silica precursor sol and / or the reaction time; the present application does not particularly limit the method for regulating the average particle size of the second hollow SiO2 material. For example, in the above step B, the average particle size of the second hollow SiO2 material can be regulated by regulating the concentration of the silica precursor sol and / or the reaction time.
[0060] The present application provides a method for preparing an anti-corrosion coating, which forms an anti-corrosion coating on the surface of an optical cable core layer. The method has the characteristics of simple preparation process and wide source of raw materials, reduces the risk of corrosion damage to the optical fiber inside the optical cable, and increases the service life of the optical cable in the application scenario of an immersion liquid-cooled data center.
[0061] Example
[0062] The total reflection film and the preparation method thereof of the embodiment of the present application will be further described below in conjunction with more specific embodiments.
[0063] Example 1
[0064] <Preparation of Anti-Corrosion Coating>
[0065] 5.0g of aluminum isopropoxide, 5.0g of perfluorooctyl triethoxysilane, 193.0g of ethanol, 1.0g of water and 0.2g of glacial acetic acid were mixed evenly at room temperature, and the mixture was kept stirred. After stirring at room temperature for 3 hours, 15g of tetraethyl orthosilicate (TEOS) was added and the stirring was continued for 24 hours. Then, a sodium hydroxide solution (concentration of 0.1mol / L) was added dropwise, and the pH value was adjusted to 11 to obtain a fluorine-silicon-modified hollow silica sol with an average particle size of 20nm, i.e., a sol containing the first hollow SiO2 material; step b, 5.0g of aluminum isopropoxide, 1.0g of perfluorooctyl triethoxysilane, 93.5g of ethanol, 1.0g of water and 0.1g of ammonia water (concentration of 25wt%) were mixed evenly at room temperature. , keep stirring, add 19.0g TEOS after stirring at room temperature for 3 hours and continue stirring for 24 hours, then add sodium hydroxide solution (concentration is 0.1mol / L), adjust the pH value to 11, and obtain fluorine-silicon-modified hollow silica sol with an average particle size of 200nm, that is, the sol containing the second hollow SiO2 material; mix the sol containing the first hollow SiO2 material and the sol containing the second hollow SiO2 material, and control the mass ratio of the first hollow SiO2 material to the second hollow SiO2 material to be 0.2:1 to obtain anti-corrosion coating slurry, and then apply the anti-corrosion coating slurry on the surface of the core layer of the optical cable, and obtain the anti-corrosion coating after drying, and the thickness of the anti-corrosion coating is 30μm.
[0066] <Optical Cable Preparation>
[0067] An inner sheath (i.e., the second protective layer), an aramid fiber layer (i.e., the buffer layer) and an outer sheath (i.e., the first protective layer) are sequentially prepared on the surface of the optical fiber having the anti-corrosion coating to form Figure 4 Optical cable of the structure shown.
[0068] Embodiment 2~embodiment 3
[0069] Except that the thickness of the anti-corrosion coating is adjusted according to Table 1 in <Preparation of Anti-Corrosion Coating>, the rest is the same as Example 1.
[0070] Embodiment 4~embodiment 5
[0071] Except that in <Preparation of Anti-Corrosion Coating>, the average particle sizes of the first hollow SiO2 material and the second hollow SiO2 material are adjusted according to Table 1, the rest is the same as Example 1.
[0072] Embodiment 6~embodiment 7
[0073] Except that in <Preparation of Anti-Corrosion Coating>, the mass ratio of the first hollow SiO2 material to the second hollow SiO2 material in the fluorine-silicon modified hollow SiO2 material is adjusted according to Table 1, the rest is the same as Example 1.
[0074] Example 8
[0075] Except that in <Preparation of Anti-Corrosion Coating>, magnesium fluoride is further added to the anti-corrosion coating slurry, and the content of magnesium fluoride in the anti-corrosion coating is regulated according to Table 2, the rest is the same as Example 1.
[0076] Embodiment 9~embodiment 10
[0077] Except that in <Preparation of Anti-Corrosion Coating>, the content of magnesium fluoride in the anti-corrosion coating is regulated according to Table 2, the rest is the same as Example 8.
[0078] Comparative Example 1
[0079] The process is the same as that of Example 1 except that the inner sheath, the aramid fiber layer and the outer sheath are directly prepared on the surface of the core layer of the optical cable, that is, the optical cable does not have an anti-corrosion coating.
[0080] Comparative Example 2~Comparative Example 3
[0081] Except that the coating thickness of the anti-corrosion coating was adjusted according to Table 1 in <Preparation of Anti-Corrosion Coating>, the rest was the same as Example 1.
[0082] Test methods and equipment
[0083] Optical fiber attenuation value test:
[0084] The optical cables were immersed in different cooling liquids and the fiber attenuation value was tested using a fiber optic spectrum attenuation meter (SA500HD) at 85°C for 500 hours.
[0085] Refractive index test:
[0086] The refractive index of the optical fiber was tested using an Abbe refractometer (ATAGO model: NAR-1T SOLID).
[0087] Table 1 Preparation parameters of Example 1 to Example 7 and Comparative Example 1 to Comparative Example 3
[0088]
[0089] Note: In Table 1, “ / ” indicates that there is no relevant preparation parameter.
[0090] Table 2 Preparation parameters of Example 1, Example 8 to Example 10
[0091]
[0092] Table 3 Performance data of various embodiments and comparative examples
[0093]
[0094] Combined with Table 3, it can be seen from Examples 1 to 9 and Comparative Example 1 that after the optical cables prepared in the present application are immersed in different types of coolants, the optical fiber attenuation values are all low, indicating that they have good protection performance against the coolant, the product reliability is good, and after long-term immersion in the coolant, the optical cable has no risk of leakage; and since Comparative Example 1 does not have the anti-corrosion coating of the present application, its optical fiber attenuation values are all high, and there is a risk of leakage.
[0095] It can be seen from Example 1 and Comparative Examples 2 to 3 that when the thickness of the anti-corrosion coating is too small (such as Comparative Example 2), the optical fiber attenuation value is high. This may be because the anti-corrosion coating thickness that is too small cannot effectively block external corrosive substances from entering the core layer and cannot play a protective role. When the thickness of the anti-corrosion coating is too large (such as Comparative Example 3), the optical fiber attenuation value is relatively high. This may be because the excessive thickness of the anti-corrosion coating causes the adhesion between the anti-corrosion coating and the core layer to decrease, which easily causes the anti-corrosion coating to peel off, thereby affecting the anti-corrosion coating's barrier effect on external corrosive substances.
[0096] It can be seen from Example 1 and Example 8 to Example 10 that the anti-corrosion coating contains magnesium fluoride, which effectively blocks external corrosive substances from entering the core layer and is beneficial to further reducing the refractive index of the optical fiber.
[0097] The above is a detailed introduction to the preparation method of an optical cable and an anti-corrosion coating for an immersion liquid-cooled data center disclosed in the present application. Specific examples are used in this article to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the technical solutions and core inventions of the embodiments of the present application; at the same time, for those skilled in the art, according to the ideas of the present application, there will be changes in the specific implementation methods and application scopes. In summary, the content of this specification should not be understood as a limitation on the present application.
Claims
1. An optical cable for an immersion liquid-cooled data center, characterized in that: The optical cable includes a core layer, in which an optical fiber is arranged, and an anti-corrosion coating is arranged on the outer surface of the core layer. The outer surface of the anti-corrosion coating also includes a cladding layer, and the anti-corrosion coating contains a fluorine-silicon modified hollow SiO2 material; the fluorine-silicon modified hollow SiO2 material includes a first hollow SiO2 material and a second hollow SiO2 material, the average particle size of the first hollow SiO2 material is 20nm~50nm, and the average particle size of the second hollow SiO2 material is 200nm~300nm; the mass ratio of the first hollow SiO2 material to the second hollow SiO2 material is (0.2~0.5):1; the thickness of the anti-corrosion coating is 1μm~100μm, and the raw material of the fluorine-silicon modified hollow SiO2 material includes perfluorooctyltriethoxysilane.
2. The optical cable according to claim 1, characterized in that The anti-corrosion coating also contains magnesium fluoride, the mass percentage of the magnesium fluoride in the anti-corrosion coating is 1% to 10%, and the mass percentage of the fluorine-silicon modified hollow SiO2 material in the anti-corrosion coating is 90% to 99%.
3. The optical cable according to claim 1, characterized in that The number of the core layer is single; Alternatively, the number of the core layers is N, and the outer surface of each core layer is provided with the anti-corrosion coating, wherein 2≤N≤32.
4. The optical cable according to any one of claims 1 to 3, characterized in that: The coating layer includes a buffer layer and a first protective layer. The buffer layer is arranged on the outer surface of the anti-corrosion coating, and the first protective layer is arranged on the outer surface of the buffer layer.
5. The optical cable according to claim 4, characterized in that The coating layer further includes a second protective layer, which is disposed between the anti-corrosion coating and the buffer layer.
6. The optical cable according to claim 5, characterized in that The Shore hardness of the first protective layer is 80A-95A, and the Shore hardness of the second protective layer is 48D-55D; and / or, the oxygen index of the first protective layer and the second protective layer is not less than 32; And / or, the material of the first protective layer and the second protective layer is selected from at least one of thermoplastic polyurethane elastomer, polyimide, polyvinylidene fluoride, polybutylene terephthalate and polyphenylene sulfide.
7. The optical cable according to claim 5, characterized in that The first protective layer and the second protective layer also contain a flame retardant, which is compounded from an organic hypophosphite flame retardant and a melamine compound; And / or, the organic hypophosphite flame retardant includes at least one of methyl aluminum hypophosphite, methylethyl aluminum hypophosphite, phenyl aluminum hypophosphite, divinyl aluminum hypophosphite, divinyl zinc hypophosphite and microcapsule-based phenyl aluminum hypophosphite, and the melamine compound includes at least one of melamine pyrophosphate, melamine polyphosphate and microcapsule-based melamine cyanurate.
8. A method for preparing an anti-corrosion coating, characterized in that: The following steps are involved: After aluminum isopropoxide, perfluorooctyltriethoxysilane, ethanol, water and glacial acetic acid are uniformly mixed at room temperature, ethyl orthosilicate is added and mixed again uniformly, and sodium hydroxide solution is added dropwise until the pH value of the system is 10-12 to obtain a sol containing the first hollow SiO2 material; After aluminum isopropoxide, perfluorooctyl triethoxysilane, ethanol, water and ammonia water are uniformly mixed at room temperature, ethyl orthosilicate is added and mixed again uniformly, and sodium hydroxide solution is added dropwise until the pH value of the system is 10-12 to obtain a sol containing a second hollow SiO2 material; The prepared sol containing the first hollow SiO2 material and the sol containing the second hollow SiO2 material are mixed according to a target ratio to obtain a sol containing the fluorine-silicon modified hollow SiO2 material; The sol containing the fluorine-silicon modified hollow SiO2 material is coated on the surface of the optical cable core layer, and an anti-corrosion coating is obtained after drying. The average particle size of the first hollow SiO2 material is 20nm~50nm, and the average particle size of the second hollow SiO2 material is 200nm~300nm; the mass ratio of the first hollow SiO2 material to the second hollow SiO2 material is (0.2~0.5):1; the thickness of the anti-corrosion coating is 1μm~100μm.
Citation Information
Patent Citations
Article comprising a mesoporous coating having a refractive index profile and methods for making same
CN101379416A
Fluorosilicone material for super-hydrophobic coating and its preparation method and use method
CN103224719A
Full dry type bending-resistant pipeline output cable and manufacturing method thereof
CN105974538A
Cable material capable of being immersed in fluorinated cooling liquid and preparation method thereof
CN114805999A
Extensible transfer film for surface coating, process for producing it, and process for applying it
US20100272990A1